Long-term exposure to glucose and lipids inhibits glucose-induced insulin secretion downstream of granule fusion with plasma membrane. - Olofsson, C; Collins, S; Bengtsson, M; Eliasson, L; Salehi, A; Shimomura, K; Tarasov, A; Holm, C; Ashcroft, F; Rorsman, P (2007)
Mouse beta-cells cultured at 15 mmol/l glucose for 72 h had reduced ATP-sensitive K+ (K(ATP)) channel activity (-30%), increased voltage-gated Ca2+ currents, higher intracellular free Ca2+ concentration ([Ca2+]i; +160%), more exocytosis (monitored by capacitance measurements, +100%), and greater insulin content (+230%) than those cultured at 4.5 mmol/l glucose. However, they released 20% less insulin when challenged with 20 mmol/l glucose. Glucose-induced (20 mmol/l) insulin secretion was reduced by 60-90% in islets cocultured at 4.5 or 15 mmol/l glucose and either oleate or palmitate (0.5 mmol/l). Free fatty acid (FFA)-induced inhibition of secretion was not associated with any major changes in [Ca2+]i or islet ATP content. Palmitate stimulated exocytosis by twofold or more but reduced K+-induced secretion by up to 60%. Basal (1 mmol/l glucose) K(ATP) channel activity was 40% lower in islets cultured at 4.5 mmol/l glucose plus palmitate and 60% lower in islets cultured at 15 mmol/l glucose plus either of the FFAs. Insulin content decreased by 75% in islets exposed to FFAs in the presence of high (15 mmol/l), but not low (4.5 mmol/l), glucose concentrations, but the number of secretory granules was unchanged. FFA-induced inhibition of insulin secretion was not associated with increased transcript levels of the apoptosis markers Bax (BclII-associated X protein) and caspase-3. We conclude that glucose and FFAs reduce insulin secretion by interference with the exit of insulin via the fusion pore.